THE FEEDBACK ANALYSIS OF EXCAVATED ROCK SLOPE - Chen S.H.; Chen S.F.; Shahrour I.; Egger P. (My University, 2001)
In this paper a methodology of the feedback analysis on the mechanical parameters and stability of the slope excavated in rock masses is presented. The method is based on the combination of the elasto-viscoplastic finite element method and the complex shape minimum method. Special attention has been paid to the simulation of the variation of parameters because of the blasting damage and the stress relief relaxation, and the de-coupling of parameters as well. The slope excavated in the granite rock masses situated at the ship lock of the Three Gorges Project is studied, from which the mechanical parameters of the rock masses and the deformation, as well as the stability of the rock slope are forecasted in time as the going on of the slope excavation.